Cognitive and Neurolinguistic Perspectives on Arabic Sentence Processing in Native and Non-Native Speakers / المنظورات المعرفية والعصبية اللغوية في معالجة الجمل العربية لدى الناطقين بها وغير الناطقين بها - Wilson. F; Fadilah Zahra (IJAS: International Journal of Arabic Studies, 2025)
his study investigates the cognitive and neurolinguistic aspects of Arabic sentence processing among native and non-native speakers. Using a mixed-methods approach, the research integrates behavioral experiments and neuroimaging techniques (EEG and fMRI) to analyze differences in sentence comprehension and processing strategies. The participants included 30 native Arabic speakers (L1) and 30 advanced Arabic learners (L2), ensuring linguistic diversity.The results revealed significant differences in reaction time and accuracy between native and non-native speakers, with L2 learners exhibiting longer processing times and lower comprehension accuracy, particularly in syntactically complex sentences. Neuroimaging data indicated distinct brain activation patterns, with native speakers relying on automatic syntactic processing while non-native speakers showed increased reliance on working memory-related areas. The findings also highlighted cognitive strategies used by non-native speakers to compensate for linguistic challenges, including reliance on lexical cues and contextual inference. These results have important implications for Arabic language instruction, suggesting that curriculum design should incorporate targeted strategies to enhance syntactic parsing efficiency among L2 learners. While the study provides valuable insights, limitations such as sample size and experimental conditions warrant further longitudinal research to track changes in sentence processing over time.